Book Review: Analyzing Digital Discourse: New Insights and Future Directions - Daniel Pascual (Universitat Jaume I. Department of English Studies, 2020)
Analyzing Digital Discourse: New Insights and Directions, edited by Bou-Franch and Garcés-Conejos Blitvich, provides orchestrated accounts of current trends in 'digital discourse', which seek to understand up-to-date communicative situations occurring online and the manifold affordances at users' disposal. At the core of the volume lies the necessity to comprehend the latest technological evolutions enacting new forms of digital interaction, which should lead to adapt traditional approaches and adopt innovative, suitable methods to identify and analyse users' semiotic and discursive practices. Such changes and adaptations are empirically examined in a plethora of digital genres and media from several sociocultural and interpersonal contexts. Therefore, the studies deployed in the book will be undoubtedly of interest to researchers of digital communication and of its prominent medium- and user-dependent characteristics, from several interdisciplinary perspectives including, inter alia, Computer-Mediated Communication (CMC) and Discourse Analysis (CMDA), ethnography, pragmatics, sociolinguistics, multimodality, social media analysis and pedagogy. Following the introductory chapter by the editors, the remaining chapters are thematically organised in sections which single out the study of digital discourse from four different vantage points: historical development, multimodality, face and identity, and ideologies triggered by language and media.